El oro azul y su gestión de pérdidas en Colombia (2019)
Water, known as blue gold, is one of the most important natural resources in the world, since on the planet only 3% of water is fresh and of this only 1% is accessible for human consumption. This is why countries establish public policies and control mechanisms to generate awareness and achieve that more and more contribute to saving and efficient use of the resource and in turn in the reduction of water stress. Colombia, in spite of being a country without water scarcity, promotes and establishes policies of control and efficiency in the management and use of water; this is why in 2014 resolution CRA 688 is issued as a guideline for a new tariff scheme, where a standard of efficiency is established for the management of water losses (commercial and technical). In 2017, Colombia loses 43.6% of the water it produces and with the new tariff framework, the programs for recovery of losses implemented by the ESP are described and the steps to be followed by a country that wishes to manage savings and efficient use of the resource are concluded.